The Investigation of CO2 Gas Sensing Performance of ZnO Nanorods Growth on RF Sputtered Seed Layer - BULUT, Fatih; ÖZTÜRK, Özgür; ACAR, Selim (Gazi University, 2023)
In this study, one-dimensional ZnO nanorod structures with different ratios of nickel doping were produced using the hydrothermal method. The presence of nickel doping in different ratios caused variations in the fundamental characteristics of the nanorods that grew on the RF sputtered seed layer, such as crystallinity quality, morphology, diameter of the nanorods, band gap energy, resistance of the sample, and CO2 gas sensing. Produced samples were found to form like hexagonal rods and crystallize in a wurtzite structure, and the ratio of nickel doping improved the crystallin quality and the morphology of sample surface. This study showed that the 5% nickel doped sample provided the most effective results in sensing CO2 gas at different concentrations. Overall, the study provided valuable insights into the relationship between doping system and the basic characteristics of wurtzite-type hexagonal ZnO.
Keywords: Semiconductors; Mikroskopi; Mühendislik; Zinc Oxide; Nanorod; Hydrothermal; CO2 Gas Sensor; Nickel Doping; Yarı İletkenler; Kimya